1994
DOI: 10.1177/073168449401300205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polymer Structure on the Gas Permeability of Model Polyurethanes

Abstract: In the face of impending CFC elimination, a large variety of low-boiling alternate blowing agents have come under scrutiny for use in rigid foam insulation applications. The permeability of both the alternate blowing agent and atmospheric gases through the rigid foam thermoset polymer contributes to the rate at which the k -factor of the resulting foam deteriorates.In this study, a compression molding method for synthesizing polymer films from polyurethane formulation components (a variety of diols with pure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The permeability of the gas molecules is determined by the T g of polymer. Low T g rubbery polymers usually, need lower energy to create microcavity for gas molecules diffusion as compared to high T g glassy polymer 27. By considering this fact, it could be speculated from our CO 2 diffusivity data that blending PS into SEBS could decrease the CO 2 permeability and thus, minimize the foam shrinkage.…”
Section: Resultsmentioning
confidence: 87%
“…The permeability of the gas molecules is determined by the T g of polymer. Low T g rubbery polymers usually, need lower energy to create microcavity for gas molecules diffusion as compared to high T g glassy polymer 27. By considering this fact, it could be speculated from our CO 2 diffusivity data that blending PS into SEBS could decrease the CO 2 permeability and thus, minimize the foam shrinkage.…”
Section: Resultsmentioning
confidence: 87%
“…This enhanced the gas permeability of the polymer as well as its capability to sorb solvents. Kaplan and Tabor [22] have shown that humidity increased the oxygen permeability of thermoset polyurethane films having glass transitions near or below 25°C. The effects of water vapor on chain mobility in polymers with affinity for water have been documented [23].…”
Section: Resultsmentioning
confidence: 98%
“…In addition, environmental conditions such as moisture also affect the diffusion rate of R11. For example, using an FTIR techmque, Nguyen et al [7] determined values of Dff at 60°C to be 10.1 X 10-8, 22.2 X 10-a and 38.4 X 10-' cm2/s for Rll in rigid PIR foam exposed to relative humidities of < 10, 60, and 75%, respectively. Furthermore, the mass change of the foam is a function of the amount and density of the constituent gases within the cell cavities.…”
Section: Resultsmentioning
confidence: 99%
“…This is unfortunate since previous studies [25] showed that the gas diffusion coefficient through polyurethane membranes depends on the type of polyol used, whereas the influence of the isocyanate functionality has not been clearly observed. Since D c,i and S c,i may vary by several orders of magnitude from one polyurethane foam to another [25], any reliable assessment of gas diffusion models through polyurethane foams should be performed for polyurethane foams made out of the same polyol. For instance, Alsoy [15] used the experimental data for the diffusion coefficient of an unknown type of polyurethane membrane [16] to validate the Bart and Du Cauzé de Nazelle's model against the experimental data taken from other studies without checking if the polyurethane foams were generated using the same polyol.…”
Section: Validation Against Experimental Datamentioning
confidence: 93%
“…Note that the specific type of polyols used for polyurethane foams is rarely mentioned and often unknown to the authors [17]. This is unfortunate since previous studies [25] showed that the gas diffusion coefficient through polyurethane membranes depends on the type of polyol used, whereas the influence of the isocyanate functionality has not been clearly observed. Since D c,i and S c,i may vary by several orders of magnitude from one polyurethane foam to another [25], any reliable assessment of gas diffusion models through polyurethane foams should be performed for polyurethane foams made out of the same polyol.…”
Section: Validation Against Experimental Datamentioning
confidence: 99%